Hemodynamics‐driven deposition of intraluminal thrombus in abdominal aortic aneurysms. (7th October 2016) - Di Achille, P.; Tellides, G.; Humphrey, J. D.
Abstract: Accumulating evidence suggests that intraluminal thrombus plays many roles in the natural history of abdominal aortic aneurysms. There is, therefore, a pressing need for computational models that can describe and predict the initiation and progression of thrombus in aneurysms. In this paper, we introduce a phenomenological metric for thrombus deposition potential and use hemodynamic simulations based on medical images from 6 patients to identify best‐fit values of the 2 key model parameters. We then introduce a shape optimization method to predict the associated radial growth of the thrombus into the lumen based on the expectation that thrombus initiation will create a thrombogenic surface, which in turn will promote growth until increasing hemodynamically induced frictional forces prevent any further cell or protein deposition. Comparisons between predicted and actual intraluminal thrombus in the 6 patient‐specific aneurysms suggest that this phenomenological description provides a good first estimate of thrombus deposition. We submit further that, because the biologically active region of the thrombus appears to be confined to a thin luminal layer, predictions of morphology alone may be sufficient to inform fluid‐solid–growth models of aneurysmal growth and remodeling. Abstract : Accumulating evidence suggests that intraluminal thrombus plays multiple, detrimental roles in the natural history of abdominal aortic aneurysms. Relying on a phenomenological metric for thrombus deposition potential, we introduce an optimization method to determine the growth of the thrombus into the lumen. This optimization is based on the expectation that thrombus growth will continue until increasing hemodynamically induced frictional forces prevent any further cell or protein deposition. Comparisons between predicted and actual intraluminal thrombus in 6 patient‐specific aneurysms suggest that this phenomenological description provides a good first estimate of thrombus deposition